Effect of trade and manufacturer traceability on the environmental performance of local companies in emerging economies. Issue 4 (28th November 2018) - Barash‐Harman, Yael
Abstract: This paper shows that manufacturer traceability triggers environmental standard diffusion from highly to weakly regulating countries, driving local companies to meet environmental regulation requirements. The paper aims to explain firms' environmental performance by using product differentiation as an indicator for manufacturer traceability. The findings show that differentiated goods sold to international markets prompt local firms to meet environmental regulation requirements and produce positive pressure to go beyond local compliance levels. However, when traceability is low, as in the case of undifferentiated goods, trade with global markets does not tend to create incentives for environmental investment. The study examines firms in the emerging economy of India.